WRKY Transcription Factors: Molecular Regulation and Stress Responses in Plants - Phukan, Ujjal J.; Jeena, Gajendra S.; Shukla, Rakesh K. (Frontiers in Plant Science, 2016)
Plants in their natural habitat have to face multiple stresses simultaneously. Evolutionary adaptation of developmental, physiological and biochemical parameters give advantage over a single window of stress but not multiple. On the other hand transcription factors like WRKY can regulate diverse responses through a complicated network of genes. So molecular orchestration of WRKYs in plant may provide the most anticipated outcome of simultaneous multiple responses. Activation or repression through W-box and W-box like sequences is regulated at transcriptional, translational and domain level. Because of the tight regulation involved in specific recognition and binding of WRKYs to downstream promoters, they have become promising candidate for crop improvement. Epigenetic, retrograde and proteasome mediated regulation enable WRKYs to attain the dynamic cellular homeostatic reprograming. Overexpression of several WRKYs face the paradox of having several beneficial affects but with some unwanted traits. These overexpression-associated undesirable phenotypes need to be identified and removed for proper growth, development and yeild. Taken together, we have highlighted the diverse regulation and multiple stress response of WRKYs in plants along with the future prospects in this field of research.